2020
DOI: 10.3390/sports8050060
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Power Assessment in Athletes: Are Cycling and Vertical Jump Tests Interchangeable?

Abstract: Regularly assessing anaerobic power is important for athletes from sports with an explosive strength component. Understanding the differences and overlap between different assessment methods might help coaches or smaller-scale testing facilities maximize financial and temporal resources. Therefore, this study investigated the degree to which cycling sprint and vertical jump tests are interchangeable for determining peak mechanical leg power output in strength-trained athletes. Professional skiers (n = 19) perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
1
8
0
2
Order By: Relevance
“…This study also found signi cant improvements of 9.4% in jump height. These results suggests that for young active adults low-volume CT may be enough to increase vertical jumping capacity, which is related to the anaerobic potency of lower limbs [31]. This chronic adaptation can be explained by improving the voluntary neural activation speed, related to the motor neuron recruitment speed and maximal motor unit discharge rate [32].…”
Section: Discussionmentioning
confidence: 81%
“…This study also found signi cant improvements of 9.4% in jump height. These results suggests that for young active adults low-volume CT may be enough to increase vertical jumping capacity, which is related to the anaerobic potency of lower limbs [31]. This chronic adaptation can be explained by improving the voluntary neural activation speed, related to the motor neuron recruitment speed and maximal motor unit discharge rate [32].…”
Section: Discussionmentioning
confidence: 81%
“…Unlike field-based athletes [ 18 ], peak power (absolute and relative) did not display acceptable inter-week reliability in the current population when using the mean of three CMJ trials. This contrasting finding is unsurprising in a cycling population due to the fatigability of anaerobic power in response to cycling load [ 6 , 19 ], resulting in high variations in cycling peak power [ 19 , 20 ], which is strongly related to vertical jump performance [ 7 9 ], including jump-derived peak power [ 7 ]. This concept partly explains why peak power measures displayed poor inter-day and -week reliability in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Cabang olahraga sepeda sangat penting untuk membutuhkan vertical jump (Gross & Lüthy, 2020). Begitu juga cabang olah raga lainnya seperti, bolabasket, bolavoli, sepakbola dan lain sebagainya.…”
Section: Hubungan Imt Dengan Vertical Jumpunclassified